Aplicação de indicadores de sustentabilidade à zona costeira do município de João Pessoa-PB - Almeida, Diego Ribeiro (2013)
Sustainability indicators are powerful tools that merge qualitative and quantitative aspects of multiple dimensions, thus guiding actions, giving support and assessing the progress toward the development sustainable. It is essential to apply these indicators in areas where there are large anthropogenic pressure as the coastal zone, where 40% of the world population lives. The research aim is to assess the degree of sustainability of the coastal zone of João Pessoa / PB through sustainability indicators. Therefore, we set the following specific goals: selecting indicators that are relevant to depict the degree of sustainability of the area; calculate the sustainability index of the region through the Dashboard of Sustainability Method and propose recommendations that can improve the indicators performance. The studies were conducted at the coastal zone of the João Pessoa / PB. Featuring stretch of 24 km the region is bordered to the north by the Bessa neighborhood and to the south by the Barra Gramame neighborhood. Were selected 17 indicators for that region and they can be divided into four dimensions: environmental, social, economic and institutional. The results demonstrate the sustainability index of the region was found at the intermediate level. However, when a comparison is made between the north area and south area we can observe some differences. On the southern coast of the region this index was found between the bad and the intermediate zone, while on the northern coast the sustainability index was found between the intermediate and reasonable zone. From these results we could produce an evaluation on the coastal area of João Pessoa that includes the social, economic, environmental and institutional dimensions and allow us to develop interventions aimed at improvements towards sustainability, as well as promoting a better insight into the complexity factors involved negatively on the stability of natural ecosystems present in the coastal zone of João Pessoa.